Risky behaviour: a rare complication of an uncommon disease in a returning traveller. (9th October 2013) - Pimenta, Dominic; Democratis, Jane
Abstract : A 49-year-old man with a history of hypertension and no known drug allergies was admitted with a 4-day history of fever, general malaise, sore throat and diarrhoea. Eleven days ago, he had returned from a 2-week adventure holiday to South Africa. On admission, he was noted to have a creatinine 392 µmol/L, alanine aminotransferase 133 IU/L, alkaline phosphatase 211 IU/L and platelets 151×10 9 /L. A differential diagnosis of suspected leptospirosis or bacterial sepsis was made and he was started on ceftriaxone. Two hours later he became hypotensive, tachypnoeic with severe myalgia and a temperature of 41°C, type I respiratory failure and metabolic acidosis. There was no stridor, facial swelling or rash. A diagnosis of Jarisch-Herxheimer reaction was made. A second dose of ceftriaxone was given without any reaction. The patient thereafter completed 7 days of doxycycline. PCR confirmed leptospirosis and subsequent leptospirosis IgM was positive. He improved clinically with treatment and was discharged after 10 days of admission.